Consumo de mel fornece proteção contra alterações motoras e moleculares induzidas por hipóxia/reperfusão em Drosophila melanogaster - Cruz, Litiele Cezar da (2017)
Honey is a complex product produced by honeybees from nectar, being widely used for its sweetening properties, as well as for its benefits to human health. Honey presents anti-inflammatory, hypoglycemic and antioxidant properties. Hypoxia followed by reperfusion is a condition triggered in several pathologies and can culminate with oxidative tissue damage. The fruit-fly, Drosophila melanogaster, has hypoxia tolerant characteristics and homology with vertebrate from pathways involved in the cascade of cellular responses for hypoxia/reperfusion. Considering these aspects, the main objective of this work was to evaluate the possible protective effect of honey produced in the Brazilian Pampa Biome on changes induced by hypoxia/reperfusion in Drosophila melanogaster, with emphasis on oxidative stress. Wild flies were treated with a diet containing 10% honey for 3 days and subsequently submitted to hypoxia conditions (3hs). After reperfusion of oxygen, parameters of survival, behavior, oxidative stress as well as mRNA expression of genes related with metabolic, inflammation and death pathways were evaluated. The results demonstrated that the honey tested is composed of compounds with antioxidant activity that were recognized both in vitro and in vivo. Hypoxia/reperfusion induced an increase in the regulation of mRNA expression of Sima (HIF-1), NFκB, Nrf2, HOX, AKT-1, INR, dILP2, dILP5 and HSP27. Indeed, flies submitted to hypoxia/reperfusion has a expression decreased of EWG and Opa-1. Honey was able to reestablish the expression of Opa-1, a gene related to mitochondrial fusion. Honey treatment also reduced the changes induced by hypoxia/reperfusion in parameters of survival, locomotor deficits, wing position, reactive oxygen species (ROS) production, GST, caspases and mitochondrial complex I activities. The results obtained here show, for the first time, the beneficial effects of honey against changes induced by hypoxia/reperfusion in Drosophila melanogaster. This study evidenced that that the honey from the Brazilian Pampa Biome has a high quality and a significant antioxidant activity in vivo, which can be related with its beneficial effects against hypoxia/reperfusion. In addition, we consider the honey as well as Drosophila melanogaster promising targets for studying pathologies associated with oxidative stress and hypoxia/reperfusion.